Identification of Technological Parameters for Vegetable Tanning of Paiche Skin Leather (Arapaima gigas) With Quebracho (Schinopsis balansae) and Mimosa (Acacia dealbata) Extract for Environmentally Sustainable Industrial Use - Moreno Ríos, Christiaan Errol (2023)
Paiche farming in the Peruvian Amazon yields sufficient raw material to produce leather; however, these skins pose a pollution problem due to their limited exploitation. This research highlights the importance of employing mechanical and chemical procedures to obtain high-quality leather. Different concentrations of quebracho and mimosa extract were used to process paiche skin. The resulting leather was strong and malleable, exhibiting a flexural strength of over 30,000 flexes without deformation, higher tear strength in treatments T1 (146.23 N) and T5 (143.12 N), and higher tensile strength in T4 (16.62 N/mm2). The leather also had an ash content of less than 1%, moisture content of less than 9%, and chromium oxide content of less than 1.5%. The effluents from the process were treated and found to have acceptable pH, conductivity, and COD values.